Separation and purification of plant terpenoids from biotransformation - Linhao Chen (Wiley-VCH, 2021)
Abstract The production of plant terpenoids through biotransformation has undoubtedly become one of the research hotspots, and the continuous upgrading of the corresponding downstream technology is also particularly important. Downstream technology is the indispensable technical channel for the industrialization of plant terpenoids. How to efficiently separate high‐purity products from complex microbial fermentation broths or enzyme‐catalyzed reactions to achieve high separation rates, high returns and environmental friendliness has become the focus of research in recent years. This review mainly introduces the common separation methods of plant terpenoids based on biotransformation from the perspectives of engineering strain construction, unit separation technology, product properties and added value. Then, further attention was paid to the application prospects of intelligent cell factories and control in the separation of plant terpenoids. Finally, some current challenges and prospects are proposed, which provide possible directions and guidance for the separation and purification of terpenoids and even industrialization.